2013
DOI: 10.1097/qai.0b013e31829b6298
|View full text |Cite
|
Sign up to set email alerts
|

Anal Human Papillomavirus Infection Among HIV-Infected and Uninfected Men Who Have Sex With Men in Beijing, China

Abstract: To determine prevalence, genotypes and predictors of anal human papillomavirus (HPV) among HIV-infected and uninfected men who have sex with men (MSM) in Beijing, China. In 2010–2011, we recruited MSM (age range 18–61; median 28 years) through peer volunteers, and collected demographic/behavioral information via interviewer-administrated questionnaires. Trained health workers collected anal swabs for HPV genotyping by PCR and blood samples for HIV/syphilis serologies . We obtained anal specimens from 212 HIV-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
61
2
8

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(85 citation statements)
references
References 42 publications
14
61
2
8
Order By: Relevance
“…Our baseline prevalence of anal HR-HPV infection in those co-infected with HIV, was similar to the prevalence observed in Australia (94%) [12] and higher than those reported from North America (ranging from 56% to 80%) [7-9], Europe (ranging from 65% to 79%) [10-11], Asia (ranging from 58% to 61%) [13-14], and the summary prevalence of 74% (95% CI, 64-83) from a meta-analysis [15]. Although the Australian study had a similar prevalence, its study population significantly differed in their age composition and sexual risk behavior.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Our baseline prevalence of anal HR-HPV infection in those co-infected with HIV, was similar to the prevalence observed in Australia (94%) [12] and higher than those reported from North America (ranging from 56% to 80%) [7-9], Europe (ranging from 65% to 79%) [10-11], Asia (ranging from 58% to 61%) [13-14], and the summary prevalence of 74% (95% CI, 64-83) from a meta-analysis [15]. Although the Australian study had a similar prevalence, its study population significantly differed in their age composition and sexual risk behavior.…”
Section: Discussionsupporting
confidence: 83%
“…Most prevalence studies of anal HR-HPV in HIV-infected MSM have occurred in North America, Europe, Australia and Asia [8-14]. A meta-analysis of cross-sectional studies primarily from the United States estimated the pooled prevalence of any HPV was higher in HIV-positive as compared to HIV-negative MSM (93% vs. 64%) [15].…”
Section: Introductionmentioning
confidence: 99%
“…A large-scale epidemiological survey identified age differences among HPV-infected individuals in different regions and populations (34). In line with this, the present study also found that the HR-HPV infection rate differs among different age groups.…”
Section: Discussionsupporting
confidence: 78%
“…The risk of HPV among men who have sex with men (MSM) is higher than among heterosexual men [3, 4]. HIV-infected MSM have an even higher risk [57]. Among MSM, HPV infection also varies by anatomic site: more common in the perineal/perianal region and anal canal than in the penile urethra or scrotum.…”
Section: Introductionmentioning
confidence: 99%